THE INFLUENCE OF LIFESTYLE, TRUST AND PRODUCT VARIATIONS ON CONSUMER SATISFACTION (STUDY ON CONSUMERS OF RESTO COFFE ANTARA MANTAN SEMARANG) - Jaka Bayu Pamuji; Bambang Sutedjo (Jurnal Ekonomi, 2023)
The purpose of the study was to analyze the influence of lifestyle variables on consumer satisfaction, the influence of trust variables on consumer satisfaction and the influence of product variation variables on consumer satisfaction.the object of this study is Resto Coffe Antara Mantan Semarang. The type of research conducted is quantitative research. The number of samples in this study was 84 Consumers of Resto Coffe Antara Mantan Semarang. The technique used in data collection is to use questionnaires. By using data analysis techniques that include descriptive statistical testing, data quality, classical assumptions, influences, and hypotheses. The results of the research obtained are Lifestyle has a positive and significant effect on consumer satisfaction, Trust has a positive and significant effect on consumer satisfaction and Product variations have a positive and significant effect on consumer satisfaction.